PENGARUH ROA DAN ROE TERHADAP PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN RITEL BEI TAHUN 2019 - 2023 - Damayanti, Putri; Handayani, Miranti (Manajerial dan Bisnis Tanjungpinang, 2025)
The retail sector in Indonesia was under significant pressure from 2019 to 2023 due to the impact of the pandemic and changes in consumer behaviour, which increased the risk of corporate bankruptcy. This study uses the Altman Z-Score model to analyse the effect of return on assets (ROA) and return on equity (ROE) on bankruptcy prediction in retail companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was adopted, using secondary data from the annual financial statements of 14 retail companies over a five-year period (2019–2023), resulting in 70 observations. The analysis methods employed include multiple linear regression tests, t-tests, F-tests and classical assumption testing. The results showed that ROA has a positive and significant effect on Z-Score, while ROE has a negative and significant effect. Both variables simultaneously have a significant effect on bankruptcy prediction. These findings confirm that ROA and ROE are important indicators of potential bankruptcy. Therefore, it is important to properly monitor and manage these profitability indicators in order to support strategic decision-making in the face of business pressures, particularly in the retail sector.